Evaluation of Assays to Measure Aminoglycosides in Serum: Comparison of Accuracy and Precision Based on External Quality Assessment. Issue 5 (October 2020) - Li, Mengya; Ma, Lingyun; Chen, Chaoyang; Lei, Lili; Zhai, Xingyu; Luo, Daohuang; Zhou, Ying; Cui, Yimin
Abstract : Background: Aminoglycosides require highly accurate therapeutic drug monitoring owing to their narrow therapeutic windows and toxic side effects. Therapeutic drug monitoring varies in different laboratories, and this difference is mainly due to the use of different analytical techniques. This study aimed to compare the accuracy and precision of immunoassays for the measurement of gentamicin, tobramycin, and amikacin in serum. Methods: Human plasma samples were spiked with known concentrations of amikacin, gentamicin, and tobramycin and dispatched to laboratories worldwide. The percentage deviation and coefficient of variation were calculated to compare the accuracy and precision among immunoassays and among antibiotics. Results: We analyzed 273, 534, and 207 amikacin, gentamicin, and tobramycin measurement results, obtained satisfactory rates of 83.9%, 86.3%, and 93.7%, and coefficients of variation ranging from 1.1% to 15.6%, 2.9% to 25.2%, and 1.8% to 27.0%, respectively. The percentage deviation ranged from −7.5% to 6.6%, −20.8% to 18.7%, and −33.2% to 41.5% for amikacin, gentamicin, and tobramycin, respectively. Significant differences were observed in accuracy and precision among assays for all antibiotics. Conclusions: This study demonstrated high variations in results obtained from antibiotic assays conducted at different laboratories worldwide.